PERLINDUNGAN KONSUMEN TERKAIT DENGAN PAJAK PERTAMBAHAN NILAI DAN SERVICE CHARGE DI RESTORAN - Adolfina Blegur Laumuri, Junia; Putrawan, Suatra (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 01, Februari 2014, 2014)
This paper titled Consumer Protection related to Value-Added Tax and Service Charge at the Restaurant, which also become the main problem to be discussed in this paper. This paper uses normative method by analyzing the problem with statue and related literature. The conclusion of this paper is that consumers get protection from three aspects, among others: Act Number 8 Year 1999 concerning Consumer Protection, supervision from institution that related to consumer protection and punishment.
Keywords: Value-Added Tax, Service Charge, Restaurant’s Enterpreneur and Consumer Protection